The coming of materials science - Cahn, R. W. (Robert W.), 1924-2007. (Amsterdam : New York : Pergamon, 2001)
The Coming of Materials Science both covers the discipline of materials science, and draws an impressionistic map of the present state of the subject. The first chapter examines the emergence of the materials science concept, in both academe and industry. The second and third chapters delve back into the prehistory of materials science, examining the growth of such concepts as atoms, crystals and thermodynamics, and also examine the evolution of a number of neighbouring disciplines, to see what helpful parallels might emerge. The book contains numerous literature references. Many refer to the earliest key papers and books, while others are to sources, often books, offering a view of the present state of a topic. Early references are to the past but as the book continues, it brings the reader up to date with more recent sources. The author, Professor Robert Cahn FRS, has striven to be critical about the history of the discipline of materials science and to draw general conclusions about scientific practice from what he has discovered about the evolution of materials science. Further issues that the book highlights include: What is a scientific discipline? How do disciplines merge and differentiate? Can a discipline also be interdisciplinary? Is materials science a real discipline? A large range of themes is presented in the book and readers are invited to interact with the author if they reach alternative conclusions. This book is not just for reading and reference, but exists to stimulate thought and provoke discussion as well.
Preface -- Preface to second printing -- Introduction -- The emergence of disciplines -- Precursors of materials science -- The virtues of subsidiarity -- The escape from handwaving -- Characterisation -- Functional materials -- The polymer revolution -- Craft turned into science -- Materials in extreme states -- Materials chemistry and biomimetics -- Computer simulation -- The management of data -- The institutions and literature of materials science -- Epilogue.
Includes bibliographical references and indexes.
Keywords: Materials science; Electronic books